Molecular Diagnosis of Felis catus Gammaherpesvirus 1 (FcaGHV1) Infection in Cats of Known Retrovirus Status with and without Lymphoma - Alicia J. McLuckie; Vanessa R. Barrs; Scott Lindsay; Mahdis Aghazadeh; Cheryl Sangster; Julia A. Beatty (Viruses, 2018)
The pathogenicity of Felis catus gammaherpesvirus 1 (FcaGHV1), a common infection of domestic cats, is unknown. To explore an association between FcaGHV1 detection and feline lymphoma, a retrospective, cross-sectional, disease-association study was conducted. The infection status of all cats for feline immunodeficiency virus and feline leukaemia virus was determined. Neither a molecular diagnosis of FcaGHV1 nor whole-blood FcaGHV1 load was related to outcome in 122 lymphoma cases compared with 71 controls matched for age and sex. Molecular analysis of lymphoma-derived DNA paired with autologous uninvolved tissue did not suggest restriction of FcaGHV1 DNA to tumour tissue. FcaGHV1 DNA detection was associated with significantly shorter survival in lymphoma cases, an observation that could not be adequately explained by treatment differences. In addition, regressive feline leukaemia virus infection was identified as a risk factor for lymphoma. A history of fighting or roaming was identified as a novel epidemiological risk factor for FcaGHV1 detection, lending support to intercat aggression as a potential route of transmission. Studies investigating the cellular location and expression of FcaGHV1 are indicated to assist in ruling out a lymphomagenic role for this virus. Prospective investigation of FcaGHV1 DNA detection as a prognostic marker in feline lymphoma is warranted.